Disinfection of the flexible fibreoptic bronchoscope against Mycobacterium tuberculosis and M gordonae. Issue 10 (October 1984) - Davis, D; Bonekat, H W; Andrews, D; Shigeoka, J W
Abstract : In view of recent reports of contamination of the fibreoptic bronchoscope by tuberculous and non-tuberculous mycobacteria, we evaluated the disinfecting properties of aqueous glutaraldehyde (Cidex) and an iodophor (Prepodyne) against Mycobacterium tuberculosis and M gordonae. We found that a 15 minute disinfection procedure with either agent, coupled with initial vigorous mechanical cleaning of the bronchoscope and its accessories, is a quick and reliable method for preventing the contamination of the bronchoscope with mycobacteria.